Participatory communication strategies for poverty alleviation in remote indigenous communities - Muniruddin; Hajji, Zul; Lauli, Rahmad A. (Jurnal Studi Komunikasi, 2024)
This study investigates the poverty alleviation approach employed by social services in Medan and the influence of remote indigenous community projects. Poverty results in several social and economic issues, underscoring the importance of identifying and implementing effective strategies to alleviate these challenges. This study investigates the impact of moral communication and social support on poverty reduction. It assesses the effectiveness of social support for communities using integrated data on prosperous families (in Bahasa called DTKS). The study employed a descriptive qualitative research methodology. The researchers obtained data by conducting interviews, observations, and analysing documents. Social services employ Islamic communication strategies to address poverty, encompassing various forms of social assistance. Only localities with integrated data on prosperous families can receive this funding. Social services employ this approach to diminish poverty and empower the community. For isolated indigenous tribes, social services extend beyond Islamic communication to implement policies that provide practical vocational training programmes that promote work integration and technical oversight. This study examines the utilisation of Islamic communication and social agencies’ assistance to combat poverty. It also provides guidance for policies and activities specifically targeted towards indigenous communities. These discoveries can provide valuable insights for shaping future social service practices and regulations.